(untitled) (Journal on studies and research of academic knowledge, 2017)
Argentina is one of the countries with the highest consumption of palm hearts worldwide, with a supply assured by imports. Depending on the possibility of developing local production with the native species Euterpe edulis and alternative species, the following technicals studies were developed. In the first study, survival and height growth at 42 months of Juçara palm (Euterpe edulis Mart.), Alexandra palm (Archontophoenix alexandrae (F. Muell) H.Wendl & Drude), Cunningham palm (Archontophoenix cunninghaniana H.Wendl & Drude and A.cunninghaniana x A.alexandrae hybrid. The study was carried out in the locality of Cerro Azul, Misiones, Argentina, in semicontrolled conditions of half artificial shade at 80%, irrigation and complete fertilization. The design was in randomized blocks with 4 replicates, heights were analyzed by variance (P> 0.05), the differences between species were studied and the means were compared by the LSD test (P>0.05) .The survival was homogeneous for all the species with values of 93.75, 98.95 and 100%, with respect to the height the species and hybrids of Archontophoenix were significantly superior with values of 87.80, 95.40 and 98.45 cm with respect to the 49.80 cm of the juçara palm. In the second study in the same locality was evaluated the survival, height growth and palm hearts production at the age of 7 years of A.alexandrae and A.cunninghaniana implanted in autumn and spring, under trees shade(100trees. ha-1). The design was in randomized blocks with 4 replicates, heights were analyzed by variance (P>0.05), differences between species and weather stations of implantation were studied, means were compared by LSD test (P>0,05). Survival was higher for both species implanted in autumn with values of 75 and 78%, in that the heights were higher with 221 and 252cm, as well as the percentages of palm trees suitable for palm hearts with values of 61 and 75.7%.